2010
DOI: 10.1038/nn.2704
|View full text |Cite
|
Sign up to set email alerts
|

Principles governing recruitment of motoneurons during swimming in zebrafish

Abstract: Locomotor movements are coordinated by a network of neurons that produces sequential muscle activation. Different motoneurons need to be recruited in an orderly manner to generate movement with appropriate speed and force. However, the mechanisms governing the recruitment order have not been fully clarified. Here we show, using an in vitro juvenile/adult zebrafish brainstem-spinal cord preparation, that motoneurons are organized in four pools with specific topographic locations and are incrementally recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
122
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 42 publications
8
122
2
Order By: Relevance
“…We recently showed that the mechanisms controlling the recruitment of motoneurons are changing during maturation. In juvenile/adult zebrafish, motoneurons that are responsible for slow swimming display specific membrane properties and receive larger synaptic drive, but their order of recruitment is not correlated with their input resistance as shown in larvae (Gabriel et al, 2011). The fact that the juvenile/ adult zebrafish in vitro preparation can sometimes display both swimming activity and escape will further allow for examination of the mechanisms of recruitment of the neurons involved and whether they are dedicated to one or shared between different motor circuits (Svoboda and Fetcho, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the mechanisms controlling the recruitment of motoneurons are changing during maturation. In juvenile/adult zebrafish, motoneurons that are responsible for slow swimming display specific membrane properties and receive larger synaptic drive, but their order of recruitment is not correlated with their input resistance as shown in larvae (Gabriel et al, 2011). The fact that the juvenile/ adult zebrafish in vitro preparation can sometimes display both swimming activity and escape will further allow for examination of the mechanisms of recruitment of the neurons involved and whether they are dedicated to one or shared between different motor circuits (Svoboda and Fetcho, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the juvenile/ adult zebrafish in vitro preparation can sometimes display both swimming activity and escape will further allow for examination of the mechanisms of recruitment of the neurons involved and whether they are dedicated to one or shared between different motor circuits (Svoboda and Fetcho, 1996). While the activity of motoneurons recruited at slow swimming frequency seems to be interrupted during escape, the primary and dorsal secondary motoneurons, thought to mediate escape, continue to receive phasic synaptic inputs during swimming (Gabriel et al, 2008(Gabriel et al, , 2009(Gabriel et al, , 2011. In addition, it is possible that different interneurons are also taking part in the initiation, maintenance, and termination of the swimming episode.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell-body diameters spanned a relatively narrow range, ruling out the possibility that different regions of the myotome might be served by MNs with separate thresholds based exclusively on the size principle (25). An elegant recent study in zebrafish larvae on how neurons are recruited during different speeds of locomotion revealed a dorsoventral ordering of MNs (10), an organization that persists in the adult (26). Ventral MNs are active at low fictive swimming frequencies, and there is a progressive and orderly recruitment of more dorsal MNs as swim speed increases.…”
Section: Discussionmentioning
confidence: 99%
“…2D). In normal development (and presumably also in the absence of activity), MNs become functionally differentiated such that, by stage 42, they (i) can fire multiple impulses in each cycle of swimming; (ii) may " drop out" of the rhythm as it slows down and weakens, but become available if swimming speeds up and intensifies; and (iii) form a more heterogeneous pool comprising members with distinct electrical properties and synaptic drive, similar to zebrafish (10,26). This combination of changes provides the larval rhythm with increased flexibility because the intensity and frequency of rhythmic activation of the muscles can change dramatically on a cycle-by-cycle basis.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal cord acts as an interface to process descending commands from the brain and sensory inputs from the periphery (5,8,(10)(11)(12)(13)(14)(15)(16). Many insights into the organization and function of circuits underlying motor behavior have been gained from studies of spinal networks controlling locomotor movements (6,13,(17)(18)(19)(20)(21)(22)(23)(24). The basic locomotor activity requires the interplay of ipsilateral excitatory drive and crossed inhibition, which ensures the alternating pattern between the two sides of the spinal cord.…”
mentioning
confidence: 99%